Homogenized and stigmatized: A discourse analysis of Asian sub-ethnic medical school aspirants - Salman H. Choudhry; Keegan D’Mello; George Kim; Robin Mackin; Amrit Kirpalani (PLoS ONE, 2025)
The study examines the influence of Asian sub-ethnic identity on the experiences of pre-medical students in the United States and Canada, aiming to understand how early interactions with the medical education system shape their pursuit of medicine. The researchers analyzed 132 discussion threads from popular online premedical school forums between June 2018 and 2023. The Asian Critical Theory framework guided the analysis along with cyclical inductive coding. Two major themes emerged: the homogenization of diverse Asian sub-ethnicities and external pressure related to sociocultural values. Terms like “over-represented minorities” contributed to the perception of Asians as a monolithic group, while expressions such as “Asian Parents” highlighted unique familial expectations. Non-Asian users often dismissed these barriers, reinforcing the model minority myth. The study emphasizes the negative consequences of framing Asians as a homogenous group in medical school admissions policies, perpetuating stereotypes, and overlooking the diversity within Asian sub-ethnic communities. The term “overrepresented” is critiqued for its role in homogenizing Asian identities and undermining the complexity of their experiences. These findings highlight the need for greater recognition of the nuanced challenges faced by Asian sub-ethnic medical trainees and the importance of dismantling stereotypes in medical education.